Basicities of primary arylamines and calculated amine nitrogen electronic charges - LEITE,Sérgio Roberto de Andrade (1998)
Mülliken charges on nitrogen atoms were calculated for several arylamines, utilizing the AM1 Quantum Chemistry method, relating their values to experimental amine pKa . Direct relation between pKa and nitrogen charges was found. The amines energies of protonation, calculated by the same method, also correlate directly with these charges.